Kajian Ummahat tentang Perempuan, Ilmu dan Rumah Tangga pada Guru SD IT Iskandar Muda Yayasan Bumi Serambi : UMMAHAT STUDY ON WOMEN, SCIENCE AND HOUSEHOLD AT YBSM PEKANBARU TEACHERS - Erna Dewi; Muhammad Ichsan (Catimore: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service aims to equip teachers / teachers with knowledge about the study of women, science and household as well as other things about women. This service was carried out for the teachers of SDIT Iskandar Muda Yayasan Bumi Serambi Mekkah (YBSM) Pekanbaru. After this debriefing is carried out, it is hoped that the teachers will have in-depth knowledge about the success and role of a woman in life, both as a career woman and as a housewife who chooses to stay at home. Before carrying out the service, the resource persons first coordinated with the school to find out the situation in the field before going directly to the field. This activity is carried out with the opening stages, material delivery, question and answer and closing.